Sound practice in government debt management - Blommestein, Hans J. (Henry Stewart Talks, 2009)
Most fundamental functional objectives of government debt management, Central government debt versus general government debt, The public debt management strategy, Debt strategy and risk management, Risk management governance, Basic notions of asset and liability management, Link between risk based public debt management and bond market, What is contingent debt?, Rules and procedures for issuing guarantees